Efficacy of diagnostic hysteroscopy in postmenopausal women (Research, Society and Development, 2022)
Diagnostic hysteroscopy is the gold standard method in endometrial evaluation, allowing direct visualization of the entire uterine cavity, besides the identification of pathologies and biopsy of suspicious lesions. To evaluate the efficacy of diagnostic hysteroscopy in postmenopausal women. An analytical cross-sectional study, developed in a university hospital. The sample consisted of 188 patients who underwent diagnostic hysteroscopy from September 2014 to September 2017. Hysteroscopy was compared with ultrasonography and anatomopathological results. Univariate and bivariate statistics were calculated. The mean age of the patients was 59.6±7.7 years and the mean time of menopause was 11.2±8 years. Hysteroscopy showed a higher sensitivity for detection of endometrial polyp (91.8%) and greater specificity in the exclusion of hyperplasia (61.4%). The main indication of the examination was endometrial thickening (72.3%) and the main finding was polypoid formation (45.7%). For asymptomatic patients, ultrasonography showed 100% and 100% of sensitivity and 10.6% and 36.2% of specificity using 5 to 9 mm as cutoff, respectively, for the diagnosis of atypical hyperplasia/endometrial cancer. Patients with atypical hyperplasia or cancer had a greater thickness (p=0.012). There was no correlation between bleeding time and endometrial cancer. Hysteroscopy was effective in the diagnosis of endometrial polyps. The main indication of the examination was endometrial thickening and the main hysteroscopic finding was endometrial polyp. Greater limit of endometrial echo thickness can be proposed in asymptomatic postmenopausal women for the indication of hysteroscopy.